Peta Kendali Atribut Menggunakan Zero-Inflated Generalized Poisson - Ratmila Mammi; Erna Tri Herdiani; Nasrah Sirajang (ESTIMASI: Journal of Statistics and Its Application, 2023)
If the variable is a discrete random variable with Poisson distribution, the data analysis must fulfill the equidispersion assumption. In reality, these assumptions are not fulfilled because the variance is greater than the mean which is called overdispersion. Overdispersion in data can occur due to the proportion of excess zero values in these variables. To estimate the parameters, the MLE method can be used on data that has a certain distribution by maximizing the likelihood function, it obtained is implicit or nonlinear so that it cant be solved analytically. To get the numerical solution, it solved by using the EM algorithm. The estimation results of the ZIGP distribution parameters are used to create control chart limits for the 2016 Neonatal Mortality Rate data in Makassar with limits of , , and . The  chart ARL value is , which is greater than the chart ARL value, which is  which indicates that the  chart is better at detecting outliers.